2017
DOI: 10.4049/jimmunol.1601179
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Crystals Induce Placental Inflammation and Alter Trophoblast Function via an IL-1–Dependent Pathway: Implications for Fetal Growth Restriction

Abstract: Excessive placental inflammation is associated with several pathological conditions, including stillbirth and fetal growth restriction (FGR). While infection is a known cause of inflammation, a significant proportion of pregnancies have evidence of inflammation without any detectable infection. Inflammation can also be triggered by endogenous mediators, called damage associated molecular pattern (DAMPs) or alarmins. One of these DAMPs, uric acid is increased in the maternal circulation in pathological pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 45 publications
6
71
0
2
Order By: Relevance
“…Our in‐vitro studies in placental explants and trophoblasts confirmed functional activity of the NLRP3 inflammasome pathway. This is the first study demonstrating cholesterol crystal‐mediated NLRP3 activation in trophoblasts, as inflammasome responses have only been shown previously for uric acid, ATP and nigericin in these cells . NLRP3 inflammasome activation requires an already exaggerated inflammatory setting, as a priming signal is needed to achieve sufficient intracellular levels of NLRP3 and pro‐IL‐1β .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our in‐vitro studies in placental explants and trophoblasts confirmed functional activity of the NLRP3 inflammasome pathway. This is the first study demonstrating cholesterol crystal‐mediated NLRP3 activation in trophoblasts, as inflammasome responses have only been shown previously for uric acid, ATP and nigericin in these cells . NLRP3 inflammasome activation requires an already exaggerated inflammatory setting, as a priming signal is needed to achieve sufficient intracellular levels of NLRP3 and pro‐IL‐1β .…”
Section: Discussionmentioning
confidence: 59%
“…PRR activation in preeclampsia may be induced by factors derived from maternal serum and/or within the stressed placental tissue. It has been reported that maternal serum levels of cholesterol and uric acid are elevated in pre-eclampsia and FGR [21][22][23][24][25][26][27][28], that cholesterol is accumulated in pre-eclamptic placentas [29] and that uric acid crystals activate the NLRP3 inflammasome in human placentas [30]. Trophoblast NLRP3 activation has been assigned a role in pre-eclampsia development [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus hyperuricaemia may be detrimental for graft survival by enhancing both cellular and humoral alloimmunity, especially during periods with relatively low blood levels of immunosuppressive medications. It is interesting that in the case of the naturally successful semi‐allogenic pregnancy increased urate levels have been associated with adverse events, such as preeclampsia and foetal growth retardation; and a recent study has shown that urate crystals cause NLRP3‐inflammasome and IL‐1β‐mediated placental inflammation and dysfunction leading to foetal growth retardation …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that in the case of the naturally successful semi-allogenic pregnancy increased urate levels have been associated with adverse events, such as preeclampsia and foetal growth retardation; and a recent study has shown that urate crystals cause NLRP3-inflammasome and IL-1β-mediated placental inflammation and dysfunction leading to foetal growth retardation. 27 Another more convincing study about the role of uric acid in triggering alloimmunity is derived from the field of bone marrow transplantation. In an experimental blood marrow transplantation, intestinal commensal bacteria and uric acid contribute to NLRP3-inflammasome-mediated IL-1β production, while gastrointestinal decontamination and uric Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal inflammation is detrimental for the developing fetal brain and can result in lifelong complications for surviving children, including cerebral palsy, autism spectrum disorder, and schizophrenia 4,10‐12 . Infections account for 20%‐30% of all causes of preterm birth and are a well‐known cause of inflammation‐induced fetal brain injury 13‐23 . The remaining preterm births and fetal brain injuries have no detectable infectious origin, suggesting that inflammation may be involved 24‐27 …”
Section: Introductionmentioning
confidence: 99%